PLAP-1/Asporin Regulates TLR2- and TLR4-induced Inflammatory Responses. (December 2015) - Yamaba, S.; Yamada, S.; Kajikawa, T.; Awata, T.; Sakashita, H.; Tsushima, K.; Fujihara, C.; Yanagita, M.; Murakami, S.
Periodontal ligament–associated protein 1 (PLAP-1)/asporin is an extracellular matrix protein preferentially expressed in periodontal ligaments. PLAP-1/asporin inhibits the cytodifferentiation and mineralization of periodontal ligament cells and has important roles in the maintenance of periodontal tissue homeostasis. However, the involvement of PLAP-1/asporin in inflammatory responses during periodontitis is poorly understood. This study hypothesized that PLAP-1/asporin might affect the pathogenesis of periodontitis by regulating periodontopathic bacteria-induced inflammatory responses. Proinflammatory cytokine expression induced by Toll-like receptor 2 (TLR2) and TLR4 was significantly downregulated when PLAP-1/asporin was overexpressed in periodontal ligament cells. Similarly, recombinant PLAP-1/asporin inhibited TLR2- and TLR4-induced proinflammatory cytokine expression in macrophages. We also confirmed that NF-κB activity induced by TLR2 and TLR4 signaling was suppressed by the addition of recombinant PLAP-1/asporin. Furthermore, IκB kinase α degradation induced by TLR4 was reduced by PLAP-1/asporin. Immunoprecipitation assays demonstrated the binding abilities of PLAP-1/asporin to both TLR2 and TLR4. Taken together, PLAP-1/asporin negatively regulates TLR2- and TLR4-induced inflammatory responses through direct molecular interactions. These findings indicate that PLAP-1/asporin has a defensive role in periodontitis lesions by suppressing pathophysiologic TLR signaling and that the modulating effects of PLAP-1/asporin might be useful for periodontal treatments.